FAKTOR-FAKTOR YANG MEMPENGARUHI WISATAWAN MENGINAP DI VILLA - I Wayan Pantiyasa (Institut Pariwisata dan Bisnis Internasional, 2012)
Petitenget area is known for tourist region where villas are established for accomodating guests.Â This study is aimed to determine what factors affect guests staying at villas in Petitenget area. The results of this study show that factors influenceing guests staying at villas in Petitenget area are classified into 4 factors. These factors include a) the competence factor has eigenvalue of 10.8065 and with the highest value variance of the percentage of 51.4593% for the guestsâ€™ decision to stay at the villa. b) Personal factor has eigenvalue of 1.626 and the highest variance value of the percentage of 7.7442% for guests to stay at the villa. c) Image factor has eigenvalue of 1.371 and the highest percentage of 6.5289% variance for guests to stay at the villa. d) Capability factor has eigenvalue of 1.295 and the highest variance value of the percentage of 6.1651% for guests to stay at the villa. The dominant factor influencing guests to stay at the villa in Petinget area is a competence factor. In order to sustain the existence of the villa in Petitenget area, it is recommended that villa should pay attention on the dominant factors and other factors that affect the guests stay at the villa. Other things need to be considered is eestablishing good and intensive cooperation with the local communities and police department. The establishment of the community business Petitenget area can be done in the region to realize a comfortable, safe and clean villa. Improving the quality of human resources remains a priority in order to improve the quality of care. Besides that, consistent promotion both through internet and other media as well as mutual partnership with travel agents and working together with the Badung regency are important, particulary in term of regulations to make the area of Petitenget as a sustainable region for villa establishment.